Classification of fine-grained igneous, sedimentary and metamorphic rocks through structured programming (2014)
The study of rocks has become more important, because through the rocks analysis I can be obtained information that can be useful in a lot of fields from mining to construction, passing through many different action fields from materials to processes. In order to analyze the rocks is required a preliminary macroscopic examination of several samples from the field in which one is going to work. The objective of this study is to describe properties such as color, hardness, texture, etc. Then we proceed to do a microscopic analysis, for that we use thin sections that have been prepared in advance from the samples that were used in the initial macroscopic examination, in order to know more properties that can only be seen with a microscope. From this analysis of the optical properties of minerals and mineral associations we can define the type of rock, the formation environments and the behavior of these, among other properties that are outstanding when carrying out a work in a field.